2021
DOI: 10.1371/journal.pone.0248852
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged grief and posttraumatic stress disorder following the loss of a significant other: An investigation of cognitive and behavioural differences

Abstract: Background Cognitive behavioural correlates to bereavement-related mental health problems such a Prolonged Grief Disorder (PGD) and Posttraumatic Stress Disorder (PTSD) are of theoretical and clinical importance. Methods Individuals bereaved at least six months (N = 647) completed measures of loss-related cognitions and behaviours (i.e., loss-related memory characteristics, negative appraisals, coping strategies, grief resilience, and perceived social disconnection) and measures of PGD and PTSD symptoms. Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…This result reflects the need for future longitudinal studies to understand the trajectory of normal grieving and its relationships with post-traumatic stress symptoms over time. Whereas, studies with participants diagnosed with prolonged grief disorder have shown associations between this disorder and post-traumatic symptoms, including hyperarousal ( 42 ), the link between normal grieving and arousal trajectory, considering time since loss, is still scarce. More evidence is required considering the causes of death (natural vs. unnatural causes), the presence of a traumatic vs. a non-traumatic loss ( 43 ), and the closeness with the deceased person.…”
Section: Discussionmentioning
confidence: 99%
“…This result reflects the need for future longitudinal studies to understand the trajectory of normal grieving and its relationships with post-traumatic stress symptoms over time. Whereas, studies with participants diagnosed with prolonged grief disorder have shown associations between this disorder and post-traumatic symptoms, including hyperarousal ( 42 ), the link between normal grieving and arousal trajectory, considering time since loss, is still scarce. More evidence is required considering the causes of death (natural vs. unnatural causes), the presence of a traumatic vs. a non-traumatic loss ( 43 ), and the closeness with the deceased person.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling experimental variables such as time elapsed between trauma and intervention and adherence to the intervention protocol will be critical. The presence of grief should also be controlled, considering that it could elicit distinct cognitive correlations than traumatic events without a loss (Smith, Ehlers, & Sar, 2021 ), moderating PFA’s effect. Furthermore, it may be worth investigating if combining PFA with other promising interventions such as Tetris or corticosteroids enhances its effect.…”
Section: Discussionmentioning
confidence: 99%
“…found gender, level of education and type of lossspecifically losing a child (Yes/No) and losing a partner (Yes/No) to be associated with higher grief. Other research has reported months since loss and experience of a violent loss as predictors of grief severity (Lobb et al, 2010;Smith & Ehlers, 2021). Therefore, mediation analyses are reported after adjusting for gender, education, losing a child or a parent, violent loss and months since loss.…”
Section: Discussionmentioning
confidence: 99%